Understanding the awareness, perception and practices of community healthcare workers for high risk antenatal cases: A survey conducted in India - Archita Ghosh; Sayantani Ghosh; Joy Dutta; Rashmi Sinha; Jayanta Mukherjee; Nishant Chakravorty (Elsevier, 2021)
Objectives: According to WHO, almost 15% pregnant women face the risk of developing complications during their gestational period. Although, the UN-mandated Millennium Development goal has prompted India to move towards achieving lower Maternal Mortality Ratio, almost 44,000 women die annually from high-risk pregnancy. Methods: The study delves into investigation with respect to the conditions of anemia, gestational diabetes mellitus and preeclampsia, which are most common and critical in such cases of high-risk pregnancy. The score-based questionnaire is used as a study instrument to assess the perception of ASHA workers towards these particular conditions. Data was recorded for all 90 ASHA workers who interact on a regular basis with pregnant women. Results: Our study showed that ASHA workers had average perception in GDM and preeclampsia, and above average perception in the condition of anemia. Knowledge gaps were observed in the referral management and practices of healthcare workers towards severely anemic patients. The healthcare workers had inadequate knowledge in the condition of GDM, its risk factors, the screening tests and threshold values to identify diabetes. Healthcare workers were not highly acquainted with the measurement of blood pressure, its standard reading, repeated measurement techniques, follow up urine tests for high blood pressure inflicted patients. Conclusions: The results suggest ASHA workers have limited knowledge in high-risk pregnancy cases and there might be a need for better training among healthcare workers and almost 90% of them had responded positively to the necessity of a portable screening device. There was observed no significant difference in the mean perception scores amongst subjects with respect to their age, education level and experience in the profession.